Imagin for reality - Edward Hopperin the cinematography - Mincheva, Boryana (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
Each frame of the movie is a picture of all the elements it contains. There is storyline, composition, lightness, proportions and perspective, color and balance of all components. Edward Hopper (1882-1967) is an American realism artist, a modern impressionist, graphic and illustrator. He is one of the greatest American painters. The text looks at the parallel between Hopper’s works and his influence in the cinematography. Based on the film „Shirley: Visions of Reality“, Austria, 2013, 93 min, color director: Gustav Deutsch.